MICROFINANCING - A KEY FACTOR IN THE DEVELOPMENT OF SMALL BUSINESSES - Xalilova Gulnora Nabiyevna (Modern American Journals, 2025)
In this article, we will look at the role of microfinance in the development of small businesses and private entrepreneurship, as well as its economic and social significance. Special attention will be paid to current problems in this area in the Uzbek economy, such as limited access of small businesses to bank loans, lack of sufficient guarantees and high interest rates. We will analyze how microfinance mechanisms can help solve these problems. In addition, we will propose measures to improve financial support for small businesses, simplify the lending process, and introduce a system of government guarantees. We argue that microfinance not only provides entrepreneurs with start-up capital, but also contributes to ensuring economic and social stability. This is achieved by reducing poverty, increasing employment, and increasing the economic activity of women and low-income groups.
Keywords: Microfinance, small business, entrepreneurship, financial integration, bank loans, guarantees, economy of Uzbekistan, economic development.